Geologi dan Pengaruh Struktur Kekar Terhadap Kestabilan Lereng Desain Pit Pada Tambang Terbuka Batubara Kecamatan Lawang Kidul, Kabupaten Muaraenim, Sumatra Selatan - Riswandi, Herry; Fitri, Arnia (Jurnal Ilmiah Geologi PANGEA, 2024)
Open pit mining system is one of the systems used to exploitation coal resources by stripping the overburden to produce slopes. Unstable slopes will result in landslides. Fractures are one of the causes of landslides. The purpose of the study was to determine the geological and geotechnical conditions of the area to create an optimal and safe slope design. The research area is administratively located in Tanjung Lalang, Lawang Kidul District, Muara Enim Regency, South Sumatra Province, which is a mining business permit (IUP) area of PT Bukit Asam Tbk. Geographically located at the geographical coordinates 103° 49'0 "BT - 103° 50'20" BT and 3° 50'59" LS - 3° 50'9" LS. The research methods used are literature studies, geological mapping, profiles, Scanlines, data analysis, rock mass rating, RQD, RMR, SMR, GSI, kinematic analysis, and quantitative analysis to determine the FK (Safety Factor) value. The research area is included in the South Sumatra basin which is included in the Muara Enim Formation which consist of Muara Enim mudstone units aged Middle - Late Miocene, and Alluvial units aged Holocene in the form of loose material accumulation. The geological structure that developed in the research area is a left slip fault with SE-NW emphasis and fractures that have NE-SW direction emphasis. At observation location 7 has an RQD value of 22.2543%, RMR 48.4210, SMR 46.81, GSI 40.8654, at observation location 10 has an RQD value of 35.1343%, RMR 52.642 8, SMR 49.17, GSI 48.2671, at observation location 24 has an RQD value of 57.2979, RMR 64.375, SMR 61.27 and GSI 60.836 at observation location 2 has a GSI value of 30 and at observation location 16 has a GSI value of 25. Based on the results of the analysis of the FK value without the influence of fractures on Section A-A' 2.364, section B-B' 1.889 and section C-C' 2.546, the FK value with fractures on section A-A' 2.326, section B-B' 1.172 and section C-C' 1.389 based on the results of linear analysis of the influence of fractures on the decrease in FK value has a determination value of R² = 0.5836 (moderate) and the effect of the number of fractures on the decrease in FK value has a determination value of R² = 0.6948 (Strong). Based on the results of kinematic analysis on sections A-A' and C-C' have a Wedge Landslide Potential type while on section B-B' has a Toppling landslide potential type. Recommendations for increasing slope stability at LP 7 by changing the slope direction N 288ºE and slope 55º, at LP 10 slope direction N 325ºE and slope 62º, LP 24 slope direction N 005ºE and slope 44º. Positive geological potential in the research area is in the form of economical coal mines and PLTU, negative geological potential in the research area is in the form of landslides, acid mine water, air pollution and bare forests.